Zoonoser hos sällskapsdjur - Wallin, Lotta (2003)
Our companion animals can, with or without symptoms, carry infectious agents which have a potential to induce diseases in man, so called zoonoses. An immune compromised person has an increased risk of becoming infected by various agents, and thus also has an increased risk to become infected by one's own companion animals. A study was carried out within the veterinary program at SLU, Sweden, based on a questionnaire answered by 31 physicians, 31 veterinarians and interviews of 30 immune compromised persons in Sweden.